O processo enunciativo do texto literário dramático - Garcia, Edson Roberto Bogas; Catanozi, Eduardo César (Navegações, 2016)
Este artigo examina os mecanismos de enunciação do drama, uma vez que também na dramaturgia há uma voz reguladora do discurso, que conduz o sentido da obra. O enunciador do texto dramático aparece fragmentado, disperso em vários eus, escondido por entre o diálogo das personagens. Assim, a situação de enunciação, no texto de teatro, se diferencia da de outros tipos de narrativa, pois, nessa manifestação literária, normalmente não temos, como no conto ou romance, a figura de um narrador que se encarrega de direcionar o discurso. Esse processo enunciativo define a teatralidade de uma obra, separando o que é drama e o que é literatura com diálogos. A história contada no texto escrito de teatro, ou seja, a literatura dramática, deixa também ela entrever um ponto de vista, já que existe uma instância produtora do sentido. ************************************************************************************************************************************************************************************************************ The enunciating process of the dramaticliterary text Abstract: This article examines the mechanisms of the enunciation of the drama, once that in dramaturgy there is also a discourse-regulating voice, which leads the meaning of such a work. The one who enunciates the dramatic text appears fragmented, spread into several ‘I – individuals’, hidden among the characters’ dialogue. Thus, the situation of enunciation, in a theater text, differenciates itself from other types of narrative, because, for this literary manifestation, we usually don’t have as, as in a short story or novel, the role of a narrator who is in charge of managing the discourse. That enunciating process defines the theatricalism of a work, setting apart ‘what drama means’ from ‘what literature with dialogues means’. The history told in the written text of the theater, which stands for dramatic literature, it also lets itself foresee a point of view, once there is a productive request of meaning. Keywords: The drama; Enunciation; Theatricalism; Point of view